2007
DOI: 10.1373/clinchem.2006.084434
|View full text |Cite
|
Sign up to set email alerts
|

Selected Exonic Sequencing of the AGXT Gene Provides a Genetic Diagnosis in 50% of Patients with Primary Hyperoxaluria Type 1

Abstract: Background: Definitive diagnosis of primary hyperoxaluria type 1 (PH1) requires analysis of alanine:glyoxylate aminotransferase (AGT) activity in the liver. We have previously shown that targeted screening for the 3 most common mutations in the AGXT gene (c.33_ 34insC, c.508G>A, and c.731T>C) can provide a molecular diagnosis in 34.5% of PH1 patients, eliminating the need for a liver biopsy. Having reviewed the distribution of all AGXT mutations, we have evaluated a diagnostic strategy that uses selected exon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 22 publications
4
49
1
Order By: Relevance
“…Additional sequence changes on the minor allele are the presence of a 74-bp imperfect duplication in intron 1 containing the two further substitutions c.166-100A4C and c.166-96T4A [Purdue et al, 1991a], a variable number of tandem repeats (VNTR) in intron 4 [Danpure et al, 1994b], and several other single nucleotide changes-c.165116A4G (Williams and Rumsby; Waterham; this work à ), c.264C4T [Danpure et al, 1994a], c.358113C4T ], and another missense change, p.Ile340Met (c.1020A4G) in exon 10 . The catalytic activity of the minor allele is significantly less than that of the major, ranging from $50 to 64% [Lumb and Danpure, 2000;Williams and Rumsby, 2007], with the difference entirely attributable to the leucine at codon 11 [Lumb and Danpure, 2000].…”
Section: Polymorphismsmentioning
confidence: 94%
See 1 more Smart Citation
“…Additional sequence changes on the minor allele are the presence of a 74-bp imperfect duplication in intron 1 containing the two further substitutions c.166-100A4C and c.166-96T4A [Purdue et al, 1991a], a variable number of tandem repeats (VNTR) in intron 4 [Danpure et al, 1994b], and several other single nucleotide changes-c.165116A4G (Williams and Rumsby; Waterham; this work à ), c.264C4T [Danpure et al, 1994a], c.358113C4T ], and another missense change, p.Ile340Met (c.1020A4G) in exon 10 . The catalytic activity of the minor allele is significantly less than that of the major, ranging from $50 to 64% [Lumb and Danpure, 2000;Williams and Rumsby, 2007], with the difference entirely attributable to the leucine at codon 11 [Lumb and Danpure, 2000].…”
Section: Polymorphismsmentioning
confidence: 94%
“…Excessive oxalate excretion is an indicator of this disease, although the test is not specific for PH1 and may actually be misleadingly reduced in renal failure. Thus more sophisticated tests, including genetic analysis Williams and Rumsby, 2007] and/or enzymology [Allsop et al, 1987;Rumsby et al, 1997], are required to make a diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The results from the yeast assays are generally consistent with the reported activities. One exception to this was the reported in vitro activity for AGTma-R233C, which was found to show greatly reduced catalytic activity (14% of wild type) when expressed in bacteria (20). The mutation R233C causes disease when combined with the minor allele mutations P11L and I340M but is not disease-causing in the major allele background.…”
Section: Expression Of Agt Disease Variants In Yeast-yeast Alaninementioning
confidence: 95%
“…There are 150 known mutations for AGXT [67] , 16 for GRHP [26] and 15 for HOGA1 [28,5557,68] . Williams et al [69] showed that targeted analysis of the three most common mutations in AGXT (c.33_34insC, c.508G>A, and c.731T>C) provides the diagnosis in 34.5% PH1 patients while exon sequencing of exon 1, 4 and 7 increases the yield and allows diagnosis in 50% PH1 patients. Prenatal diagnosis can be done by testing chorionic villi.…”
Section: Systemic Oxalosismentioning
confidence: 99%